Necrotizing Periodontal Diseases: Multidisciplinary Perspectives on Pathogenesis, Diagnosis, and Management - Eman Alshaheen; Lina Nabhan; Moutaz Ali Alameer; Abdullah Ahmed Alamer; Salih Mohammed S. Aljasem; Mudaher Habeb Ali Alhamoud; Ali Mahdi Abdullah Al Shakes; Mohammed Hussain Alabbad; Abdulaziz Ibrahim Aldubaikhi; Refah Daifullah Alotaibi; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Necrotizing periodontal diseases (NPDs) are acute, destructive infections of periodontal tissues characterized by rapid onset, severe pain, and tissue necrosis. They encompass necrotizing gingivitis, necrotizing periodontitis, and necrotizing stomatitis, forming a continuum that can progress to noma in extreme cases. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To review the pathogenesis, clinical features, diagnostic approach, and management strategies for NPDs, emphasizing multidisciplinary perspectives and preventive measures. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This narrative review synthesizes current evidence from clinical studies, histopathologic analyses, and epidemiologic data to outline etiologic factors, microbial profiles, and therapeutic protocols. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> NPDs primarily affect immunocompromised individuals, those with malnutrition, or under severe psychosocial stress. Key risk factors include HIV infection, hematologic disorders, tobacco use, and poor oral hygiene. Microbial dysbiosis involving Fusobacterium, Prevotella, and spirochetes drives tissue destruction through synergistic virulence and host immune failure. Management centers on early diagnosis, local debridement, chlorhexidine rinses, analgesia, and systemic antibiotics when systemic involvement occurs. Long-term prognosis depends on controlling systemic and behavioral risk factors. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> NPDs represent preventable yet aggressive conditions requiring prompt intervention and interprofessional collaboration. Early recognition, risk factor modification, and structured maintenance programs are essential to prevent recurrence and severe complications such as osteonecrosis and noma.